THE REPRESENTATION OF THE VATICAN THROUGH THE LENS OF AMERICAN IDEOLOGY IN THE FILM CONCLAVE (2024) - Nurhaeni Sulastri; Krisna Sujiwa (BASIS (Bahasa dan Sastra Inggris), 2026)
This article examined how the Vatican was represented through the lens of American ideology in the film Conclave (2024) by using Stuart Hall’s theory of representation, specifically the intentional approach. The study employed a qualitative method through textual analysis of narrative structure, characters, dialogue, and visual symbols such as closed spaces, the sealing of red candles, black and white smoke, and the technological isolation procedures during the conclave to identify ideological meaning patterns embedded in the film. The analysis showed that the film deliberately constructed the Vatican as a sacred institution that also functioned as a political arena marked by secrecy, intrigue, and conflict between progressive and conservative factions, so that religious practice was shifted into a power drama in line with the typical suspicion of American ideology toward closed institutions. Characters such as Cardinal Tremblay and Joshua Adeyemi were represented as symbols of corruption, hypocrisy, and political ambition, while Cardinal Lawrence and Vincent Benitez were used to insert liberal American values such as moral individualism, transparency, inclusivity, and reform, including through the figure of an intersex Pope as a metaphor of a “new purity.” The article concluded that Conclave not only presented the Vatican as the spiritual center of Catholicism, but also intentionally projected and negotiated the hegemony of American values within the image of a transnational institution, thereby influencing how global audiences understood the relationship between sacredness, power, and ideology in cinematic representation.